Impact of Paper Information Leaflets on Dental Anxiety and Well-Being in Czech Patients: A Randomized Clinical Trial - Plachý, Robert; Krejčová, Lenka; Machoň, Vladimír; Bujda, Michele (Journal of International Society of Preventive & Community Dentistry, 2025)
AIM: Dental anxiety and well-being significantly influence patients' oral health and quality of life. This study investigated whether providing paper information leaflets (PILs) before performing dental procedures improved psychological well-being and reduced anxiety in Czech patients. MATERIALS AND METHODS: This parallel-group, single-blind randomized, prospective clinical trial was conducted at a private dental clinic in the Czech Republic in 2020. A total of 167 adult patients were randomly assigned to either the experimental group (n = 82), receiving both verbal information and a PIL, or the control group (n = 85), receiving only verbal information before their dental procedure (fillings, endodontic treatment, prosthetic restorations, or extractions). Pre- and post-procedure psychological well-being and anxiety were assessed using study-specific questionnaires. Data analysis was conducted in R using RStudio, with a significance level set at P < 0.05. Between-group differences were assessed while controlling for gender and education. Linear regression was used to analyze pre-procedure anxiety, and logistic regression was used to analyze post-procedure well-being outcomes (reporting "everything was fine," "unpleasant mouth sensations," and "quick adjustment"). The Benjamini-Hochberg correction was applied to control for multiple comparisons. Sensitivity analysis used the "best-worst and worst-best case" method to evaluate nonrandom missing data. Power analysis determined a minimum of 64 participants per group for a two-tailed t test. RESULTS: Baseline anxiety levels, measured on a 1-6 scale, were similar between the PIL group (mean 4.26, SD 1.11) and the control group (mean 4.36, SD 1.17; β = -0.11, P = 0.54). Post-procedure, while fewer patients in the PIL group reported that "everything was fine" (28/82 vs. 39/85), this difference was not statistically significant after correction for multiple comparisons (uncorrected P = 0.038, α FDR = 0.01). No significant differences were found between groups regarding "unpleasant mouth sensations" (P = 0.84) or "quick adjustment" (P = 0.52). CONCLUSION: Providing PILs in addition to verbal information did not significantly impact pre-procedure anxiety or post-procedure well-being in this sample of Czech dental patients. These findings indicate that verbal communication alone may be sufficient for managing patient anxiety and promoting well-being in this context. Further research using validated instruments and exploring different communication strategies is warranted.
Keywords: doctor-patient communication; Anxiety management; dental anxiety; well-being; information leaflet; patient education; dental care